Studies on the static behaviors of unbonded prestressed steel reinforced low-strength concrete rectangular frame beams. (15th September 2018) - Xiong, Xueyu; Yao, Gangfeng
Abstract: In this paper, four one-fifth-scale unbonded prestressed steel reinforced concrete (UPSRC) frame beam specimens were tested under vertical monotonic loading. The parameters including the amount of steel shape, ratio of rebar and the dimension of column sections were studied. The failure mode, load-deflection behavior, crack distribution, strain of rebar and steel shape were investigated. Furtherly, the tendon stress increment, ductility and post-peak load-carrying capacity of UPSRC frame beams were discussed and an analysis method was established to predict the maximum and post-peak load-carrying capacity. Test results showed that the UPSRC frame beams showed a typical beam hinge failure mode and still had good bearing capacity after the maximum load-carrying capacity. The unbonded tendons could well control the development of cracks and greatly improve the deformation restoring capacity of SRC beams. Furthermore, the value of ultimate stress increment in tendons of UPSRC members was greatly underestimated by the methods in generally design codes. By increasing the depth of web or enlarge the dimension of columns would improve the ductility of UPSRC members. Finally, the analysis method provided in the paper accurately evaluate the maximum load-carrying capacity and a little overestimate the post-peak load-carrying capacity.